The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.19945
|View full text |Cite|
|
Sign up to set email alerts
|

Screening of cancer tissue arrays identifies CXCR4 on adrenocortical carcinoma: correlates with expression and quantification on metastases using 64Cu-plerixafor PET

Abstract: Expression of the chemokine receptor CXCR4 by many cancers correlates with aggressive clinical behavior. As part of the initial studies in a project whose goal was to quantify CXCR4 expression on cancers non-invasively, we examined CXCR4 expression in cancer samples by immunohistochemistry using a validated anti-CXCR4 antibody. Among solid tumors, we found expression of CXCR4 on significant percentages of major types of kidney, lung, and pancreatic adenocarcinomas, and, notably, on metastases of clear cell ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…For CXCR4, suitable radioligands are available and have been successfully tested in lymphoproliferative malignancies (19)(20)(21). Two of these radioligands, 64 Cu-plerixafor and 68 Ga-Pentixafor, can also reliably assess the expression of CXCR4 in vivo in patients affected by ACC or aldosterone producing adenoma, respectively (4,38). Bluemel et al went a step further towards a potential theranostic use of CXCR4 and compared the performance of 68 Ga-pentixafor PET/CT with 18 F-FDG PET/ CT in 30 patients with advanced ACC (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For CXCR4, suitable radioligands are available and have been successfully tested in lymphoproliferative malignancies (19)(20)(21). Two of these radioligands, 64 Cu-plerixafor and 68 Ga-Pentixafor, can also reliably assess the expression of CXCR4 in vivo in patients affected by ACC or aldosterone producing adenoma, respectively (4,38). Bluemel et al went a step further towards a potential theranostic use of CXCR4 and compared the performance of 68 Ga-pentixafor PET/CT with 18 F-FDG PET/ CT in 30 patients with advanced ACC (3).…”
Section: Discussionmentioning
confidence: 99%
“…They are an active component of the tumor microenvironment, driving tumor-specific immune responses and promoting invasion, metastasis, stemness and resistance to chemo-and radiotherapy (1,2). Recently, expression of CXCR4 was reported in primary tumors and metastatic lesions of patients with ACC both at protein level in vitro and in vivo using radiolabeled CXCR4 ligands (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our study, expression differed in intensity and staining pattern but we obtained 82% of positive PT (93/113 animals). In human breast primary tumors, heterogeneity of expression pattern is often found and the positivity rate, is highly diverse [ 29 , 30 , 35 42 ]. This variability can be explained by the different IHC and scoring methods but also by the diversity of CXCR4 primary antibodies used.…”
Section: Discussionmentioning
confidence: 99%
“…Two promising directions that are being pursued in this regard are (1) the generation of radioactively-labeled small CXCR4 inhibitors for utilization in diagnostics and therapeutics of high CXCR4 expressing tumors [ 64 , 65 ], and (2) the usage of CXCR4 inhibitors to overcome tumor immune suppression in general and resistance to ICIs in particular [ 66 , 67 , 68 , 69 ]. With regards to the first direction, two groups have shown that labeling of the CXCR4 antagonist pentixafor with radioactive isotopes (68Ga and 64Cu) enabled the specific and accurate in vivo detection of high CXCR4 expressing tumors in the lung [ 64 , 65 ]. These findings are highly intriguing not only because they may, in the future, facilitate the selection of patients with high CXCR4 expressing tumors for anti-CXCR4 based therapeutics, but also because they open the way for labeling of CXCR4 antagonists with therapeutic radioactive isotopes such as 177Lu and 90Y for endoradiotherapy [ 70 ].…”
Section: Diagnostic and Therapeutic Potential Of Cxcr4 Antagonistsmentioning
confidence: 99%